PENERAPAN MESIN PENGADUK PADA UKM OLAHAN WALUH DI KECAMATAN GETASAN KABUPATEN SEMARANG - Sunyoto Sunyoto; Atiek Zahrulianingdyah; Rosidah Rosidah; Indah Anisykulillah (Universitas PGRI Semarang, 2020)
The aim of this activity is to solve the problems faced by SMEs engaged in processing pumpkin as a superior product of Semarang Regency, Central Java. As an activity partner is UKM